Environmental impact of biochar and wheat straw on mobility of dinotefuran and metribuzin into soils (Asian Journal of Agriculture, 2024)
Abstract. Fouad MR, El-Aswad AF, Aly MI, Badawy ME-T. 2024. Environmental impact of biochar and wheat straw on mobility of dinotefuran and metribuzin into soils. Asian J Agric 8: 57-63. The environmental effect of 5% biochar and wheat straw on the mobility of dinotefuran (DNF) and metribuzin (MBZ) in alluvial soil (A) and calcareous soil (B) was studied. The breakthrough (BTC) curves of DNF and MBZ were delayed in soil columns compared to that of iodide. The amendment of soil A or B columns with biochar and wheat straw increased the leaching of DNF collected in leachates, consequently reducing the breakthrough time. Biochar amendment increased the leaching of MBZ in soil A, whereas it significantly reduced the leaching of MBZ in soil B. Wheat straw amendment also significantly reduced the MBZ cumulative percentage. It is indicated that the downward of DNF in soil A is more rapid than that in soil B, while MBZ was faster in soil B compared to soil A; the leaching rate of MBZ is higher than DNF in all soil columns. The calculated GUS indices of DNF and MBZ were lower than 2.8, which means these pesticides are non-lechers. DNF required more water to leach from soil B than from soil A. In contrast more water was needed to leach MBZ from soil A compared to soil B. In addition, the DNF required more water for leaching from soil A or B than MBZ.
Keywords: Dinotefuran, metribuzin, mobility, soil amendments